Penerapan Standar Fasilitas Ruang Belajar Pada Taman Kanak-Kanak Katolik Santa Clara Surabaya - Melani, Florentina (Intra, 2015)
Education can be started from early age, and this early education shall be able to improve the quality of human resources which can be useful for the future. Kindergarten as the first formal education institute is an early education program where the children can learn as they play along. Kindergartens were designed to improve the intelectual, social, emotional, linguistic, and physical development. The main factor that matters the most in supporting the development of children in kindergartens are the teacherâs quality, learning activity programs, and physical environment. Physical environment refers to the childrenâs learning class along with its facility. A good learning class facility can be very important in order to support the learning proccess so it can run optimally. The goal of this research is to learn about the standard application of learning classes in Santa Clara Kindergarten Surabaya. The result achieved was that the Santa Clara Kindergarten Surabaya has already applied the standards on the classes, with the few exceptions like the studentâs table dimension and the unapplied fire protection system. Santa Clara Kindergarten Surabaya applies the learning class facility standards based on the National Education Departmentâs directive and the added foundation curriculum into the interior aspects and the learning class facilities.